The Scripture of truth - Collett, Sidney, -1941 (London, UK Marshall, Morgan and Scott, 1905)
Includes bibliographical references and index.
First published 1905. Copy 1: 18th impression ; donated by Mr M. Gregory. Copy 2: 16th impression.
Keywords: Bible -- canon; Bible -- inspiration